Analysis of the power sector in Bangladesh: current trends, challenges, and future perspectives - Sarker, Md Tanjil; Farid, Fahmid Al; Alam, Mohammed Jaber; Ramasamy, Gobbi; Karim, Hezerul Abdul; Mansor, Sarina; Sadeque, Md. Golam (Institute of Advanced Engineering and Science, 2024)
Bangladesh’s economic development is largely dependent on the power sector, which promotes sustainability and growth. The country’s future energy security, however, is seriously threatened by the natural gas reserves running out by 2028. As a result, the current energy mix has to be modified right away to ensure Bangladesh’s sustained economic growth. This research paper offers a thorough analysis of Bangladesh’s power sector’s current state. With a focus on important metrics like installed capacity, electricity generation, and distribution infrastructure, the study seeks to provide insights into the sector’s opportunities, challenges, and strengths. The research highlighting the importance of energy security and forecasting the projected energy demand in Bangladesh. The study also looks at current projects and advancements that have shaped Bangladesh’s power industry. This research also provides an ideal energy option that supports Bangladesh's sustainable growth. This analysis offers significant insights into the dynamics of the power industry in Bangladesh, elucidating it is present trajectory, the challenges it encounters, and the potential avenues for achieving a more sustainable and resilient energy future.